Tinjauan Metode Granulasi Basah dalam Formulasi Tablet Effervescent - Linda Khafidho Nur Khasanah; Cholifatus Shahroh; Aprillia Cahyaningtyas; Selviana Eka Rahma Nilasari; Rimba Setia Buana Khanza Arifin; Dewi Rahmawati (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Effervescent tablets are one of the pharmaceutical dosage forms widely developed due to their ability to enhance dissolution rate, bioavailability, and patient compliance, especially for individuals who have difficulty swallowing conventional tablets. In the formulation of effervescent tablets, an appropriate powder processing method is required to produce granules with optimal physical properties, one of which is the wet granulation method. This study aims to comprehensively review the role of wet granulation in the formulation of effervescent tablets based on literature from various scientific journals. The method used in this study is a Systematic Literature Review (SLR), with data sources obtained from electronic databases such as Google Scholar, PubMed, and ScienceDirect within the last 5–10 years. The results of the review indicate that wet granulation improves powder flowability, compressibility, and content uniformity. In addition, this method enhances the mechanical strength of tablets and improves dissolution characteristics, resulting in better quality effervescent tablets. However, wet granulation also has limitations, particularly its sensitivity to moisture, which may trigger premature effervescent reactions, as well as its relatively complex manufacturing process. In conclusion, wet granulation is an effective method for the formulation of effervescent tablets when process parameters and material selection are properly optimized.